Pyrene-Based Diarynes as Precursors for Twisted Fused Polycyclic Aromatic Hydrocarbons: A Comparison of Two Routes - Elbert, Sven M.; Baumgärtner, Kevin; Esteves, Joshua A.; Weber, Laura; Rominger, Frank; Mastalerz, Michael (Organic Materials, 2020)
Two bench-stable and readily accessible pyrene-based diaryne precursors based on triflate as well as TMS triflate motifs are introduced and compared in their [4+2]-Diels–Alder reactions with tetracyclone to give an oligophenyl-substituted dibenzo[e,l]pyrene in both cases. By single-crystal X-ray analysis, this twistacene showed helical chirality and an end-to-end contortion of 49.6° due to steric repulsion.
Keywords: polycyclic aromatic hydrocarbons; twistacene; Diels–Alder reaction; pyrenes; arynes